Thermal Performance Improvement of Solar Parabolic Dish System Using Modified Spiral Coil Tubular Receiver - Rajkumar Malviya; Prashant V. Baredar; Anil Kumar (International Journal of Photoenergy)
The present research intends to design an efficient receiver for solar thermal applications with a solar dish concentrator system. Thermal and dynamic analysis is carried out for different convolutions of a spiral coil, and experiments are performed for testing the modified absorber. Experimental results are validated for the spiral absorber with numerical results. Three receivers of different numbers of convolutions are analyzed, and simulation steps are performed for these receivers to make improvements in the system efficiency. Finally, 5 convolutions of a spiral coil tubular absorber are taken for the modified design of the system. Absorber position for every spiral convolution is kept at the focus of the concentrated solar dish collector to achieve maximum efficiency. Material used for the reflective surface is anodized aluminum and copper for the absorber. The diameter of the aperture for the parabolic dish collector is 1.4 m. The maximum absorber temperature for May month comes out to be 296°C, and the maximum working fluid outlet temperature is found to be 294.2°C which is near to simulating temperature of 289.59°C and 288.15°C, respectively. This innovative design of the absorber consists of a feature of a 5 mm extension to the spiral tube at the exit and entry; hence, the turbulence effect could be overcome. Experimental thermal efficiency was found the highest (i.e., ηthmax=75.98%) for May. This work emphasizes on improving thermal performance by obtaining optimum absorber size using convolution strategy. Investigation of 5 convolutions of spiral coil tubular absorber with extended ends for obtaining optimum performance than existing work is the superiority of this work.